2003
DOI: 10.1096/fj.02-1122fje
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin is a novel survival factor of cardiomyocytes: mitochondria as a target of 5‐HT2B‐receptor signaling

Abstract: Identification of factors regulating cardiomyocyte survival and growth is important to understand the pathogenesis of congenital heart diseases. Little is known about the molecular mechanism of cardiac functions triggered by serotonin. The link between signaling circuitry of external stimuli and the mitochondrial apoptotic machinery is of wide interest in cardiac diseases. Using cultured cardiomyocytes and 5-hydroxytryptamine (5-HT)2B-receptor knockout mice as an animal model of dilated cardiomyopathy, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 58 publications
8
108
2
3
Order By: Relevance
“…The biological activity of PAMH suggests interesting possibilities for pharmacological modulation of muscle growth and function. In addition to influencing cardiac growth and development, 5-HT 2B receptor signaling promotes myocyte survival and mitochondrial biogenesis (33). Recent studies have also revealed a profound stimulatory effect of PAMH on skeletal muscle development (unpublished results).…”
Section: Discussionmentioning
confidence: 91%
“…The biological activity of PAMH suggests interesting possibilities for pharmacological modulation of muscle growth and function. In addition to influencing cardiac growth and development, 5-HT 2B receptor signaling promotes myocyte survival and mitochondrial biogenesis (33). Recent studies have also revealed a profound stimulatory effect of PAMH on skeletal muscle development (unpublished results).…”
Section: Discussionmentioning
confidence: 91%
“…The second major result is that 5-HT 2B R could regulate numbers, morphology and function of central nervous work showing a protective function of 5-HT 2B R in newborn cardiomyocytes [50]. These studies will have to be extended to adult spinal cord microglia to determine the effect of aging, as well as the potential role of microglial location in their response to 5-HT 2B R stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The 'trophic' activity of this neurotransmitter is also demonstrated in peripheral tissues, like in vascular smooth muscle cells (VSMC) where 5-HT remains a growth-modulating factor beyond the fetal period (Kawano et al, 2001). Recently, 5-HT has also been described as a survival factor of cardiomyocytes (Nebigil et al, 2003;Nebigil and Maroteaux, 2001).…”
Section: Discussionmentioning
confidence: 99%